2020
DOI: 10.21203/rs.3.rs-86922/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Efficient SARS-CoV-2 detection in unextracted oro-nasopharyngeal specimens by rRT-PCR with the Seegene AllplexTM 2019-nCoV assay

Abstract: The fight against the COVID-19 pandemic has created an urgent need to detect and isolate infected people. The challenge for clinical laboratories has been finding a high throughput, cheap, and efficient testing method in the context of extraction reagent shortages on a planetary scale. To answer this need, we studied SARS-CoV-2 detection in nasopharyngeal swabs stored in UTM (Universal Transport Media) or RNAse-free water by rRT-PCR with the Seegene Allplex TM 2019-nCoV assay without RNA extraction. Optimal re… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 2 publications
0
7
0
Order By: Relevance
“…In attempts to detect virus, the processing, extraction, and expansion during the nucleic acid amplification test are very risky. Therefore, virus to be analysed must be inactivated before the expansion, where proteinase K serves as a key component in the virus sampling [48–50] . In light of this, we provide here an ideal molecular design to screen the reactivity of proteinase K and ensure that the viral protein is completely reacted.…”
Section: Resultsmentioning
confidence: 99%
“…In attempts to detect virus, the processing, extraction, and expansion during the nucleic acid amplification test are very risky. Therefore, virus to be analysed must be inactivated before the expansion, where proteinase K serves as a key component in the virus sampling [48–50] . In light of this, we provide here an ideal molecular design to screen the reactivity of proteinase K and ensure that the viral protein is completely reacted.…”
Section: Resultsmentioning
confidence: 99%
“…Another Canadian study demonstrated the feasibility of salivary detection of SARS-CoV-2 in the setting of a COVID-19 testing centre [19] and found a lower estimated rate of detection relative to swab testing; however, they used a different protocol, where (i) a preservative/viricidal fluid mixture was automatically released into the sealed saliva sample and (ii) the PCR assay was different. In our study, all samples were analysed using unextracted rRT-PCR after dilution, PK treatment and thermal lysis [10]. This approach saves time and costs as compared to the extracted RT-PCR.…”
Section: Discussionmentioning
confidence: 99%
“…The nCoV assay detects three viral genes: E (Envelope), RdRp (RNA-dependent RNA polymerase) and N (Nucleocapsid). Only N is typically detected when the viral load is low [cycle threshold (Ct) ≥ 35]; therefore, we used the N Ct values to compare ONPS and saliva samples [10].…”
Section: Specimen Collection and Processingmentioning
confidence: 99%
“…The flocked swab was first used to swab the posterior oropharynx and the tonsillar arches, and then the same swab was inserted through one nostril parallel to palate until resistance was met or the distance was equivalent to the distance from the patient’s ear to their nostril, rotated several times and left in place for 5 – 10 seconds prior to being removed as per Center for Disease Control instructions for collection ( 13 ). The ONPS was placed in a conical 15 ml centrifuge tube containing 3 ml of molecular water (PCR grade water), which is a validated, standard-of-care specimen transport medium for SARS-CoV-2 testing ( 12, 14 ). Subjects were then provided with 5 ml of natural spring water (Eska water, St-Mathieu-d’Harricana, Québec, Canada or Naya water, Mirabel, Québec, Canada) in a disposable soft plastic cup (Plastic Medicine Cups, AMG Medical, Montreal, Quebec, Canada) and instructed to rinse their mouth for 5 seconds, tilt their head back and gargle for 5 seconds, repeat this cycle once, expel the water back in the plastic cup and empty it in a 15 ml conical polypropylene centrifuge tube.…”
Section: Methodsmentioning
confidence: 99%